ISO document management system - Muragashan, Sivasangari; Mat Yamin, Fadhilah (Universiti Utara Malaysia, 2020)
The main purpose of this study is to create an ISO document management system in which will reduce the manual works by UUM staff. This system is proposed for replacing the existing manual system to make easier work for STML staff. The objectives of this study are to design an ISO online document to an easier way to use and to develop an online document system to reduce the manual document. This study is conducted in a qualitative method. The interview was done face to face. From the interview, it is found that computerized is a more efficient way to handle than a filing system. The staff of ISO strongly believe that online document makes an easy way to handle ISO document. It can be concluded as the online documentation must be created more changes in the future.